2022
DOI: 10.3390/pr10040664
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Distributions and Bioavailabilities of Heavy Metals in Soil in An-Tea Plantations in Qimen County, China

Abstract: Heavy metals mainly enter tea from the soil. In this study, stratified soil samples were collected, at a depth of 0–60 cm, using a soil drill in An-tea plantations. Speciation of As, Cd, Cr, Cu, Ni, Pb, and Zn was determined using the European Community Bureau of Reference sequential extraction method, and the heavy metal concentrations in the extracts were determined by inductively coupled plasma−mass spectrometry. Compared with other soil layers, the mean Cd, Cu, Pb, and Zn concentrations were highest in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Heavy metal bioavailability can be evaluated by the bioactivity coe cient (Xu et al 2022, Zhang et al 2019, usually divided into available K1 (acid soluble), potentially available K2 (reducible and oxidisable) and inert K3 (residual) based on their chemical fractions. In the underlying layer, K1 and K2 for Cr and As decreased in the order moss crust > mixed crust > algal crust > bare soil, with K3 the opposite (Fig.…”
Section: Heavy Metal Fractions and Bioavailability In The Underlying ...mentioning
confidence: 99%
“…Heavy metal bioavailability can be evaluated by the bioactivity coe cient (Xu et al 2022, Zhang et al 2019, usually divided into available K1 (acid soluble), potentially available K2 (reducible and oxidisable) and inert K3 (residual) based on their chemical fractions. In the underlying layer, K1 and K2 for Cr and As decreased in the order moss crust > mixed crust > algal crust > bare soil, with K3 the opposite (Fig.…”
Section: Heavy Metal Fractions and Bioavailability In The Underlying ...mentioning
confidence: 99%
“…Research has shown that the absorption of heavy metals and uorine by tea trees comes from water in soil (Gao et al 2012;Zhang et al 2020;Zhang et al 2021). Meanwhile, the bioavailability of uoride and lead is greatly increased in acidic tea plantation soils (Jin et al 2005; Xu et al 2022;Yang et al 2018), which also potentially increases the migration of uoride and lead from soil to tea tree and into human body through the food chain (Han et al 2006; Ruan et al 2003). Therefore, achieving the immobilization of lead and uorine in water and soil is the key to solving the combined pollution of uorine and lead in tea garden soil, which is of great signi cance for soil ecology and human health and safety.…”
Section: Introductionmentioning
confidence: 99%
“…The existing studies on the changes of the rhizosphere environment mostly focus on the changes of heavy metal content in rhizosphere soil solution and the changes of plants' effective state of heavy metals. More studies on the morphological changes of heavy metals in soil solid phase use rhizosphere bags, rhizosphere boxes, and other artificial rhizosphere environments [9,10]. This simulated rhizosphere environment is different from the growth environment of natural plants.…”
Section: Introductionmentioning
confidence: 99%